Rational, Robust, and Secure Negotiations in Multi-Agent Systems - Ito, Takayuki; Hattori, Hiromitsu; Zhang, Minjie; Matsuo, Tokuro (Studies in Computational Intelligence,, 2008)
This book addresses all aspects of negotiation mechanisms in multi-agent systems, including Multi-Issue Negotiations, Concurrent Negotiations, Strategy-proof Mechanisms, Rational Argumentation, Auctions and Voting, and so on. These issues are being explored by researchers from different communities in Multi-Agent systems. They are, for instance, being studied in agent negotiation, multi-issue negotiations, auctions, mechanism design, electronic commerce, voting, secure protocols, matchmaking & brokering, argumentation, and co-operation mechanisms. This workshop will bring together researchers from these communities to learn about each other 's approaches, form long-term collaborations, and cross-fertilize the different areas to accelerate progress towards scaling up to larger and more realistic applications.